The relationship between maternal COVID-19 with fetal and neonatal complications and intrauterine vertical transmission: A cohort study on pregnant women - Zahra Shafizadeh; Zahra Akbarian-rad; Fatemeh Nasiri-Amiri; Mostafa Javanian; Hamid Reza Nouri; Mehdi Rajabnia; Zahra Geraili; Shanaz Barat; Jamileh Aqatabar Roudbari (PLoS ONE, 2025)
Background The clinical features, maternal and fetal complications, and the potential for vertical transmission of SARS-CoV-2 infection in pregnant women are still unknown. This cohort study aimed to determine the relation of coronavirus infection to the incidence of fetal and neonatal complications by comparing outcomes in pregnant women with COVID-19 to those in non-infected pregnant women. Method This prospective cohort study was conducted on all pregnant women who gave birth between September 2020 to September 2021 at Rouhani Hospital, Iran. The case group included pregnant women infected with SARS-CoV-2, confirmed by clinical signs, symptoms and positive result of Real-time polymerase chain reaction (real-time PCR), who were followed up until 72 hours after birth. All fetal and neonatal complications, such as premature birth, oligohydramnios, fetal growth restriction, perinatal death and vertical transmission were recorded. Risk ratios for adverse pregnancy outcomes were analyzed by a modified Poisson regression model adjusted for relevant variables. Results The final sample included 234 pregnant women (100 COVID-19 infected and 134 non-infected). The mean age was 29.42 ± 6.16 years (p = 0.12), and the mean BMI (body mass index) was 26.51 ± 4.16) Kg/m2 (p = 0.30). Cesarean delivery was more common among women with COVID −19 [adjusted risk ratio (aRR): 1.12, 95% confidence interval (CI): 1.09–1.25, p = 0.03]. A significant increase was observed in neonatal intensive care unit (NICU) admission in SARS-CoV-2 infected pregnant women compared to non-infected pregnant women [adjusted risk ratio (aRR):2.46, 95% confidence interval (CI): 1.06–5.42, P = 0.034]. Neonate born to women with COVID-19 had significantly higher rate of preterm birth (22% versus 11.2%) and low 5 minutes APGAR score (2% versus 0%) significantly (P < 0.05). Nearly all newborns tested negative for SARS-CoV-2 infection after birth (97.94%). Of 76 cord blood samples tested, 16 (21.05%) and 4 (5.26%) cases of infants born to mothers infected with COVID-19 had positive IgG and IgM antibodies, respectively. Conclusions Neonates born to mothers with COVID-19 faced a significantly higher risk of cesarean delivery and NICU admission, but no significant differences in other pregnancy complications were observed between COVID-19 and non-infected groups, highlighting the complex effects of the virus on pregnancy outcomes.